CRIMINAL JURISDICTION IN SVETLANA ALEXIEICH’S VOICES FROM CHERNOBYL(2005) - Dodi Zuyandi; Kurnia Ningsih; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
The purpose of this analysis are to expose the issue about criminal jurisdiction which is done by Soviet Government and to know the contribution of the implied author in revealing criminal jurisdiction. This analysis is related to the concept of power by Michel Foucault that is supported by the text and context based interpretation. The result of this analysis shows the Soviet Government commits the criminal jurisdiction that can be seen from hiding the truth and ignoring the cictims of nuclear explosion.